2012
DOI: 10.1080/10590501.2012.681486
|View full text |Cite
|
Sign up to set email alerts
|

Assessment and Validation of US EPA's OncoLogic® Expert System and Analysis of Its Modulating Factors for Structural Alerts

Abstract: OncoLogic® is a software program able to screen chemical compounds for toxicological effects. The software predicts the potential carcinogenicity of chemicals by applying rules of structure activity relationship (SAR) analysis. To validate the predictivity of OncoLogic® (Version 7.0), 123 compounds tested with the long-term carcinogenicity bioassay on rodents were extracted from the ISSCAN database and were analyzed. The concordance between the OncoLogic® SAR analysis and the bioassay results was high. To bett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Structural alerts (SA), like an expert system, can help identify key substructures to certain toxicity and avoid potential toxic compounds in very early stages. It has been widely applied not only in drug discovery, , but also in other fields such as cosmetic research and environmental protection …”
Section: Introductionmentioning
confidence: 99%
“…Structural alerts (SA), like an expert system, can help identify key substructures to certain toxicity and avoid potential toxic compounds in very early stages. It has been widely applied not only in drug discovery, , but also in other fields such as cosmetic research and environmental protection …”
Section: Introductionmentioning
confidence: 99%
“…OncoLogic has been freely available for use by the general public for over 10 years (http://www.epa.gov/oppt/sf/pubs/oncologic.htm). Two recent external validation studies (Mayer et al, 2008;Benigni et al, 2012a) showed >90% accuracy for the two batches of substances tested. However, application of the System is limited to fibers, metals, polymers and 50 classes of organic substances and not all substituents are covered.…”
Section: Chemical / Structural Class Approachmentioning
confidence: 88%
“…No relevant structural alerts for genotoxicity were identified with the exception of the alert namely 'H-acceptor-path3-H-acceptor' detected by the profiler 'Structure Alerts for the in vivo micronucleus assay' The 'H-acceptor-path3-H-acceptor' refers to the possibility of non-covalent binding to DNA or proteins as a result of the presence of two bonded atoms connecting two hydrogen bond acceptors. However, the Panel noted that the positive predictivity of such alerts for in vivo genotoxicity was quite low, ranging from 'none' (34%) to 63% depending on the database, with a high incidence of false positives (Benigni et al, 2010(Benigni et al, , 2012.…”
Section: In Silicomentioning
confidence: 99%